Pengaruh Pertumbuhan Ekonomi Dan Pengangguran Terhadap Kemisikinan Di Kepulauan Selayar - Fitsma, Fitsmasari (ICOR: Journal of Regional Economics, 2022)
This study aims to determine the effect of economic growth and unemployment on poverty in the Selayar Islands in 2007-2021. This type of research is quantitative research with multiple linear regression method using EVIEWS software. The study was conducted in the Selayar Islands using secondary data obtained from the Central Bureau of Statistics of the Selayar Islands. The period of this research is 15 years from 2007 to 2021. The results show that economic growth partially has a negative and insignificant effect on poverty. Partial unemployment has a significant positive effect on poverty. Another result is that economic growth and unemployment simultaneously have a significant effect on poverty